Legal Analysis and Social Impact of Environmental Policy in the Modern Era Relating to Plastic Waste - Camiliya Fakhriyah Garnita; Hesti Dwi Astuti; Aji Mulyana (Perantara Law Review, 2024)
This research aims to conduct a legal analysis and evaluate the social impact of environmental policies related to plastic waste in the modern era. The legal analysis includes an examination of regulations and laws relating to plastic waste management, single-use plastic use, and environmental protection. In this context, the research also assesses the effectiveness of law enforcement and sanctions against violations of plastic-related environmental policies. The social impact of these environmental policies is analyzed through the lens of community engagement, changes in consumer behavior, and industry responses to environmental regulations. Factors such as community awareness, participation in recycling programs, and implementation of environmentally friendly practices are the focus in evaluating social impact. The results of this study highlight the complexity of plastic environmental issues in the modern era, The findings of this study are expected to provide in-depth insights into legal challenges and social impacts.